KAIDAH TAFSIR SEBAGAI PANDUAN MEMAHAMI SUMBER DASAR TAFSIR AL-QUR’AN: (Interpretation Rules as a Guide to Understanding the Basic Sources of Qur'an Interpretation) - Kholisoh (Raqib: Jurnal Studi Islam, 2025)
To understand the Qur'an correctly and avoid misinterpretation, a set of principles known as Qawaid Tafsir is required in the interpretation of the Qur'an. As a sacred text, the Qur'an has been interpreted throughout the ages, opening up opportunities to explore the divine messages contained within it using different approaches. One may face challenges that are not easy to overcome, leading to ambiguity when understanding the Quran without the guidance of an interpretation or knowledge of interpretation. The presence of principles of Quranic interpretation will undoubtedly assist in comprehending the content of the Quran broadly and deeply.  In this context, the author will briefly present an article on the principles of interpretation based on the sources that serve as references for these principles.